UNASUR, Ecuador y el orden mundial: Política internacional de drogas 2007-2015 - Vintimilla Jarrín, Diego Armando (2018)
The drug policy of the Ecuadorian State, during the period 2007-2015, has passed through structural modifications – not exempt from contradictions – which are expressed both in its local policy and in its foreign policy. These changes have been conditioned by the action of a hegemonic historical bloc lead by the US and its so-called "war on drugs" that has set the path for the development of international politics. The constitution of Unasur as a regional space for the construction of new meanings in the regional drug policy, supposes the configuration of a new field of dispute for the international politics. Furthermore, this process is conditioned by a concrete historical context in which dialectic relations are developed between the policy of the organism and the policy of its member states. The object of our research will be to identify the ways in which the Unasur-Ecuadorian State relations have been developed.